Effect of GGBFS as filler in polyester grout on strength development and flowability - Lim, S. K.; Zakaria, F.; Hussin, M. W.; Muhamad, R. (2006)
Properties of polymer grout based on isopthalic unsaturated polyester resin (IUPR), methyl ethyl ketone peroxide (MEKP), river sand and ground granulated blast furnace slag (GGBFS) have been designed, tested and discussed in this paper. Slag was used as one of the design component to investigate its effect to polyester resin systems. Mechanical properties such as compressive and flexural strength of polyester grout under different curing conditions in tropical climate have been studied. It has been noted that GGBFS can be used as a micro-filler in polyester grout systems without weakening the mechanical properties of the resin systems. 10 percent to 30 percent of slag has been used to replace river sand, and the binder sand ratio is 1 to 1.5 by weight to maintain the flowability (pumpability) of polyester grout. At the higher level of slag, viscosity of resin system increased and caused the polymer grout gelatinous (unable to pump). The isophtalic polyester grout using slag as partial of filler provided compressive strength over 100MPa and the flexural strength is above 40MPa under all curing regimes. The polyester grout can be one of the good alternatives to replace epoxy grout as structural repair material as its superior properties closer to epoxy but it is cheaper than epoxy systems.